The influence of personal values on family firm succession: a structural model. (2nd August 2019) - Camfield, Claudio; Franco, Mário
Setting out from the personal values theory of Schwartz (1992), this study aims to analyse the possible influences of personal values on the succession process in family firms. Data were collected through an online questionnaire together with a sample formed of 226 Portuguese family firms. Based on structural equation modelling (SEM), of the seven hypotheses suggested for the study, six were supported statistically, demonstrating that personal values influence the succession process in the family firm. The results suggest that personal values of a higher order (HOV) influencing succession factors are: 1) conservation influences the personal values of the predecessor and the context factor; 2) self-transcendence influences the successor's personal factors and those of relationship and process; 3) self-enhancement has an influence on the financial factor. This study also contributes to the literature on family firms, providing important results in the field of psychology for the area of management.